Socio-Economic Conditions of the Fisher Community in Sri Tanjung Village, Siantan District, Anambas Islands Regency - Agustia, Sarpika; Hidir, Achmad (CV. Rayyan Dwi Bharata, 2024)
This research was conducted in Sri Tanjung Village, Siantan District, Anambas Islands Regency. This research aims to determine the socio-economic conditions of fishing communities as seen from social conditions consisting of fishermen's education level and living conditions as well as economic conditions consisting of income and ownership of fishing gear. This research uses quantitative methods with descriptive analysis with a sample of 58 respondents. This research uses a simple random sampling technique and data collection is carried out through observation, structured interviews using questionnaires, and documentation. The research results obtained are that on the social aspect, the educational level of Sri Tanjung fishermen is still relatively low because they have only completed junior high school level, then in terms of living conditions, the majority of Sri Tanjung fishermen have their own semi-permanent houses. Meanwhile, in the economic aspect, the income earned by Sri Tanjung fishermen is classified as low, namely below the average income or UMK of Anambas, then for fishing equipment ownership status, Sri Tanjung fishermen use a fleet of boats (pompong) measuring 1 - 5 GT with fishing gear facilities. which is complete with 3 types of fishing equipment (pull fishing rod, trolling rod, and longline) and is equipped with modern technology (GPS, Fish Finder, radio, and solar panels).